Exploring the intricate interplay of epigenetic mechanisms in the pathophysiology of obesity: an overview - Suhaimi, Nur Faseeha (Universiti Putra Malaysia Press, 2023)
Epigenetics, a multifaceted and intricate scientific domain, plays a substantial role in the aetiology of noncommunicable diseases, particularly obesity. Its unique capacity to regulate gene expression and cellular processes endows it with remarkable power and potential to mitigate and investigate this global scourge. In this review, the three most widely recognised and complex epigenetic mechanisms implicated in the pathophysiology of obesity - DNA methylation, histone modifications, and non-coding RNAs, and their multifarious and complex interplay with obesity are explored. The review highlights the potential of epigenetic interventions, particularly lifestyle modifications, in managing and ameliorating obesity and related disorders and their reversibility. These interventions present a promising target for designing and developing effective and sustainable strategies to alleviate the enormous burden of obesity worldwide. The crucial insights provided by this review are indispensable for informing and shaping public health policies and interventions that aim to combat and mitigate the insidious and pernicious impact of obesity on individuals and societies.